Inter-regional metric disadvantages when comparing countries’ happiness on a global scale. A Rasch based consequential validity analysis - Diego Fernando Rojas-Gualdrón (Universidad de San Buenaventura, 2017)
Happiness has been proposed as an alternative goal in welfare analyses. Several indices have been proposed for its measurement but studies about their metric properties and validity are insufficient. In this paper, the Happy Planet Index is analyzed in terms of its consequential validity as a global health inequality indicator from the invariant measurement perspective of the Rasch model. Model fit is analyzed with emphasis on differential item functioning when comparing between world regions, and its consequential validity by comparing conclusions about the magnitude and inequalities in countries’ happiness. Main findings show enough evidences for structural and construct validity, but not for the supposed underlying score distribution; not either for its generalizability because of sever differential functioning. Conclusions about the magnitude of geographical inequalities and happiest countries substantially differed between the original index and the Rasch measure.